2005
DOI: 10.1079/pns2005468
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients in childhood and the influence of subclinical inflammation

Abstract: In the present paper biomarkers of micronutrient status in childhood and some of the factors influencing them, mainly dietary intake, requirements and inflammation will be examined. On a body-weight basis the micronutrient requirements of children are mostly higher than those of an adult, but most biomarkers of status are not age-related. A major factor that is often overlooked in assessing status is the influence of subclinical inflammation on micronutrient biomarkers. In younger children particularly the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 33 publications
6
117
0
1
Order By: Relevance
“…This means it is necessary to verify whether the vitamin A defi ciency is due to insuffi cient intake Continue or whether it is a secondary response to an infection. 20 Food intake was not assessed in this study, which can be considered a limitation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This means it is necessary to verify whether the vitamin A defi ciency is due to insuffi cient intake Continue or whether it is a secondary response to an infection. 20 Food intake was not assessed in this study, which can be considered a limitation.…”
Section: Discussionmentioning
confidence: 98%
“…2,c Infections can result in reduced serum retinol concentrations in the fi rst 24 hours after onset. The presence of sub-clinical infection may lead to VAD due to reductions in the retinol binding protein, 20 regardless of insuffi cient intake of food sources and the hepatic reserves of the vitamin. However, episodes of serious or prolonged infection may affect hepatic reserves, due to reduced food intake, lower absorption, increased biological use and abnormal urinary excretion of retinol serum.…”
mentioning
confidence: 99%
“…In vitro studies in which carotenoids are exposed to stimulated neutrophils certainly indicate that plasma carotenoids are at increased risk of destruction in such circumstances. 25,26 Furthermore, the work of Cser et al 19 and our own 20 suggests that in humans α-and β-carotene concentrations in plasma are more sensitive to oxidation than lutein concentrations and this has also been observed in in vitro studies. 27 In field studies done in free-living communities in developing countries, the volunteers recruited may be apparently healthy, but in such situations disease exposure is high and infestation by intestinal parasites is also common; thus the presence of subclinical inflammation is highly likely.…”
Section: Carotenoids and Inflammationmentioning
confidence: 68%
“…Both anaemia and low retinol concentrations are characteristic of subjects with subclinical inflammation. 4,20 A large confidence interval in the increase in serum β-carotene concentrations in the enriched-wafer group was also reported, which the authors suggested was due to a large between-individual variation in bioavailability of β-carotene. The same observation was made by Bulux et al 46 (Fig.…”
Section: Anaemic Lactating Women In West Java Indonesiamentioning
confidence: 95%
See 1 more Smart Citation